Femtosecond Laser Near-Field Reduction for Fabrication of 3D Gold Nanocluster Array Assisted by MoS2 Quantum Dots - Bai, Shi; Obata, Kotaro; Sugioka, Koji (Frontiers in Physics, 2022)
Laser-induced near-field effect, which confines the laser energy in a nano scale region to be enhanced, allows the laser fabrication with a resolution much smaller than the wavelength. Owing to such a high fabrication resolution, the laser-induced near-field fabrication has been attracting much attention as a tool for the surface nanostructuring. In this report, we introduce a novel method based on the laser-induced near-field reduction using a femtosecond laser by which gold nanocluster arrays are formed on substrates with the assistance of self-assembled silica microspheres. In the laser near-field reduction, the incident laser is focused in the vicinity of the backside of the silica microspheres to initiate synthesis of gold nanoparticles, followed by creation of gold nanoclusters by continuous growth of the gold nanoparticles along the silica microsphere surfaces. In addition, laser-treated MoS2 quantum dots are mixed in the gold precursor to increase the reduction efficiency for the formation of spherical gold nanoclusters. The gold nanocluster arrays provide potential applications for plasmonic devices.